Endolysins from Antarctic Pseudomonas Display Lysozyme Activity at Low Temperature - Orlando, Marco; Pucciarelli, Sandra; Lotti, Marina (Marine Drugs, 2020)
Organisms specialized to thrive in cold environments (so-called psychrophiles) produce enzymes with the remarkable ability to catalyze chemical reactions at low temperature. Cold activity relies on adaptive changes in the proteins' sequence and structural organization that result in high conformational flexibility. As a consequence of flexibility, several such enzymes are inherently heat sensitive. Cold-active enzymes are of interest for application in a number of bioprocesses, where cold activity coupled with easy thermal inactivation can be of advantage. We describe the biochemical and functional properties of two glycosyl hydrolases (named LYS177 and LYS188) of family 19 (GH19), identified in the genome of an Antarctic marine Pseudomonas. Molecular evolutionary analysis placed them in a group of characterized GH19 endolysins active on lysozyme substrates, such as peptidoglycan. Enzyme activity peaks at about 25-35 °C and 40% residual activity is retained at 5 °C. LYS177 and LYS188 are thermolabile, with Tm of 52 and 45 °C and half-lives of 48 and 12 h at 37 °C, respectively. Bioinformatics analyses suggest that low heat stability may be associated to temperature-driven increases in local flexibility occurring mainly in a specific region of the polypeptide that is predicted to contain hot spots for aggregation.